PENERAPAN METODE COOPERATIVE LEARNING TIPE TAI (TEAM ASSISTED INDIVIDUALIZATION)BERBASIS MULTIMEDIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN TIK - Nia Kurnia Asih, - (2010)
This paper entitled "Application of Multimedia Based Cooperative Learning Method TAI (Team Assisted Individualization) Type to Improve Students' Results in TIK Learning" is a quasi-experimental research with time series design done in Class VIII SMPN 15 Bandung in even semester of academic year 2009-2010. The aims of the research are; 1) to figure out the students' results before the application of multimedia based cooperative learning method TAI type, 2) to figure out students' improvement in TIK learning after the application of multimedia based cooperative learning method TAI type, 3) to figure out the effectiveness of TIK learning after the application of multimedia based cooperative learning method TAI type. The research data are obtained from multiple choices questions. The data show that students' learning results before the application of multimedia based cooperative learning method TAI type are low. Hypothesis test is done using Wilcoxon test because the data are not normally distributed. Based on the calculation by Wilcoxon test, the significance of 0.000 is obtained in each learning series which is lower than 0.05. It can be concluded that H0 is rejected and H1 is approved. The approved hypothesis is that there is significant improvement in students after the application of multimedia based cooperative learning method TAI type. Learning effectiveness is seen from normalized gain in each learning series which is always improving. In the first and second learning series the effectiveness of TIK learning is categorized as average and the effectiveness of TIK learning in the third series is categorized as high. This means that the model is effective for TIK learning.